7-Pyrrolidinethoxy-4′-Methoxyisoflavone Prevents Amyloid β–Induced Injury by Regulating Histamine H3 Receptor-Mediated cAMP/CREB and AKT/GSK3β Pathways - Wang, Linlin; Fang, Jiansong; Jiang, Hailun; Wang, Qian; Xue, Situ; Li, Zhuorong; Liu, Rui (Frontiers in Neuroscience, 2019)
In studies on the treatment of Alzheimer’s disease (AD), in which cognition is enhanced even modestly or selectively, it has been considered that the histamine H3 receptor (H3R) may be a potential target. In this study, we aimed at evaluating the ability of 7-pyrrolidinethoxy-4′-methoxyisoflavone (indicated as LC1405), a novel potential H3R antagonist identified from our H3R antagonist screening system, to ameliorate amyloid β (Aβ)-induced cognitive deficits, and to explore the underlying mechanisms that are related to H3R-modulated signaling. Our results demonstrated that LC1405 effectively reduced the progression of Aβ-associated disorders, such as improved learning and memory capabilities, preserved tissues from suffering neurodegeneration and ultrastructural abnormalities, and ameliorated cholinergic dysfunction in an APP/PS1 double transgenic mouse model of AD. In an in vitro model, LC1405 protected neuronal cells against copper-induced Aβ toxicity, as demonstrated by the improvement in cell viability and decrease in neuronal apoptotic ratio. In addition, treatment with LC1405 resulted in the up-regulation of acetylcholine (ACh) or histamine release and provided neuroprotection through cellular signaling cascades involving H3R-mediated cAMP/CREB and AKT/GSK3β pathways. Furthermore, the beneficial effects of LC1405 on Aβ-mediated toxicity and H3R-mediated cAMP/CREB and AKT/GSK3β axes were reversed after pharmacological activation of H3R. In conclusion, our results demonstrated that LC1405 blocked Aβ-induced toxicity through H3R-modulated signaling transduction both in vitro and in vivo. The results also suggested that LC1405 might have translational potential as a complementary therapy to control disease progression in AD patients who developed cognitive deficits with H3R-related ACh neurotransmission abnormality.